Domestic and Foreign Smart Factory Development Status and Trend Analysis - Lin, Jingxuan (Asia Pacific Economic and Management Review, 2024)
As an important development direction of modern industry and manufacturing, smart factories realize the automation, digitization and intelligence of production processes through the integration of advanced technologies such as the Internet of Things, big data and artificial intelligence. The construction of smart factories not only helps to improve production efficiency and quality, but also can meet the increasingly diversified and personalized needs of consumers, and promote the development of manufacturing in a more efficient, smarter and greener direction. This paper will analyze the development status and trend of smart factories at home and abroad in detail, in order to provide reference for relevant enterprises and policy makers.